Dictating the Risk: Experimental Evidence on Giving in Risky Environments - Brock, J. Michelle; Lange, Andreas; Ozbay, Erkut Y (American Economic Review, 2013)
We study if and how social preferences extend to risky environments. We provide experimental evidence from different versions of dictator games with risky outcomes and establish that preferences that are exclusively based on ex post or on ex ante comparisons cannot generate the observed behavioral patterns. The more money decision-makers transfer in the standard dictator game, the more likely they are to equalize payoff chances under risk. Risk to the recipient does, however, generally decrease the transferred amount. Ultimately, a utility function with a combination of ex post and ex ante fairness concerns may best describe behavior. (JEL C72, D63, D64, D81)